Le bois entre nature et surnature. Pommiers et sapins, aubépines et coudriers - Karin Ueltschi (Studia Romanica Posnaniensia, 2025)
Wood, even when cut from its stalk and thus from its nourishing sap, does not wither. It is perhaps this astonishing quality that makes it not only a sacrificial fuel of choice, but also the vector par excellence of all regeneration, resurrection and promise of eternity. Dead wood is therefore invested with paradoxical gifts. We’ll try to decipher their lesson: they are all keys giving access to meanings buried beneath the noise of speech and the linear rationality of the diegesis.